Сучасні тенденції працеохоронного менеджменту: формування фахівця нового типу з охорони праці та промислової безпеки - Мовмига, Наталія Євгенівна; Мезенцева, Ірина Олександрівна (Видавничий дім "Гельветика", 2019)
У статті розглянуто актуальні питання сучасних тенденцій формування фахівця нового типу з питань управління охороною праці та тенденції працеохоронного менеджменту сьогодення. Авторами наведено та проаналізовано статистичні дані по виробничому травматизму та професійним захворюванням по Україні за останній рік, та обґрунтовано актуальність впровадження менеджменту в область управління безпекою виробництва з метою удосконалення шляхів профілактики виробничого травматизму. У статті доводиться, що найважливіший напрям оптимізації охорони праці на підприємстві, це висококваліфіковані фахівці з охорони праці, які мають успішно працювати в умовах ринкових відносин, постійних інновацій, безперервного вдосконалювання та ускладнення професійної діяльності з додаванням управлінських функцій.

The article deals with topical issues of modern tendencies of formation of a new type of specialist in labor protection management, optimization of labor protection and actualization of labor protection management at enterprises. It is revealed that high requirements for management are put forward to enterprises and their staff, representatives of which must possess the general principles of management and specific skills and knowledge in the field of management. This is especially related to production security management issues. The statistical data on work-related injuries and occupational diseases in Ukraine over the last year are presented and analyzed. Analysis of facts of occupational injuries confirms the decisive role of a man in creating the preconditions for the formation of traumatic situations: factors associated with this are called "human factor" (by the actions of a direct executor) and the organization of work (by actions of an aggregate executor – employees and an employer). Thereby the role of labor protection management and main tendencies of modern management in market conditions are considered in the article. The article argues that the most important direction of optimization of labor protection at an enterprise is highly skilled occupational safety specialists who have to work successfully in conditions of market relations, constant innovations, continuous improvement and complication of professional activity. Technical vision of future specialist in occupational and industrial safety at the present stage must be based not only on the profound knowledge of professional and fundamental natural sciences, but also modern management technologies, competences in the field of humanitarian, social and economic activity. Professional competence and professional compliance of future professionals are key components and security prerequisites of labor safety and occupational injuries reduction. The role of modern specialists in occupational and industrial safety, who have engineering and managerial competencies in labor protection management, is defined.
Modern trends of labour protection management of formation a new type specialist in labor protection and industrial safety
Keywords: оптимізація; виробничий травматизм; професійні захворювання; управлінські компетенції; optimization; occupational injuries; managerial competences; occupational disease